Chomsky on democracy & education - Chomsky, Noam (RoutledgeFalmer, 2003)
This volume gathers a range of Chomsky's writings, some previously unpublished and not readily available to the general public. Chomsky outlines a philosophy of education steeped in the liberal tradition of John Dewey, more concerned with cultivating responsible citizens than feeding children facts. The goal of education, Chomsky argues, is to produce free human beings whose values are not accumulation and domination, but rather free association on terms of equality.